Relationship with some of the variables and measurements Elkinmetekih physical completion of the effectiveness of the javelin - mataib, Suhair (Journal of Physical Education, 2012)
The research aims to identify the relationship between some variables Elkinmetekih and measurements of physical completion of the effectiveness of the javelin to the research sample, The sample of research (5) players from the national team for junior archers spear for the year 2010, and was chosen the way intentional, was to identify some variables Elkinmetekih related to throwing Spear It (the speed of launching the spear, and the angle of launch of the spear, and the length of the last step, and the angle of the knee joint of a man front the moment of touching the ground, and the angle of the knee joint of a man front the moment the bow stretched, and the angle of the trunk when the bow stretched, and the rate of speed of approach). Were identified measurements of physical relevant javelin throwing it (the length of the arm, and the length of the trunk, and the area around the chest, and thigh circumference, and shoulder width), and after analyzing the movement through photography Alfieri a precise method for the study variables kinetic where he managed the existing study the movement of a pointing strengths and weaknesses affecting in motion, and after receiving the results of the analysis, the researcher extracted the statistical means it, and concluded the following: there is a relationship between measurements of physical (total length, chest circumference, thigh circumference, shoulder width, weight, age) level digital (xD) for the javelin to a single sample research, as well as there is a relationship between variables Elkinmetekih (the speed of starting the spear, and the length of the last step, the angle of the trunk when the bow stretched, the rate of speed approaching) level digital (xD) for the javelin of the sample individuals. The researcher recommended the following: that the selection on the physical measurements and some variables related Elkinmetekih the nature of the contest, as well as benefit from the results of this research in the planning for analysis and training in the javelin.